Validity of an online, self-administered Timeline Followback for alcohol use with adolescents - Hareskov Jensen, Natascha; Vallentin-Holbech, Lotte; Dash, Genevieve F.; Feldstein Ewing, Sarah W.; Rømer Thomsen, Kristine (Frontiers in Psychiatry, 2023)
Objective: The Timeline Followback (TLFB) is a widely used and well-validated interviewbased tool for assessing patterns of recent health risk behavior. There is some evidence of the validity of the TLFB as a self-administered online tool for assessing alcohol use, but further research is needed to establish its validity in younger populations and populations outside the U.S. Further, it is unknown how self-administered online TLFB formats compare to more timesaving and commonly used single-item alcohol questions. The primary aim of the current study was to validate a new online, self-administered TLFB for alcohol use against the TLFB interview in a sample of European (Danish) adolescents aged 16-18 years (N=30).Method: Participants completed a TLFB telephone interview, a self-administered online version of the TLFB, and single-item alcohol questions. Assessments were administered using a within-subject, counter-balanced design. Estimates of number of drinking days, binge-drinking days, maximum drinks consumed on one occasion, total drinks, and drinks per drinking day were compared across metrics.Results: All correlations between the drinking outcomes assessed via the TLFB interview and the TLFB online were positive, and statistically significant (r s s=.86-.94, p<.01). Wilcoxon signed-rank tests showed no significant differences between the TLFB interview and the TLFB online on drinking days, binge drinking days, max drinks, and total drinks. Participants reported drinking significantly more drinks per drinking day on the TLFB online (M=4.66) compared to on the TLFB interview (M=4.12) (p=.009).Overall, the results support the validity of the online, self-administered TLFB in a sample of European (Danish) adolescents.